Formation of fines during the pelleted feed manufacturing process and the resulting differences in nutrient composition of fines and pellets - De Jong, Jon A.; DeRouchey, Joel M.; Tokach, Michael D.; Goodband, Robert D.; Woodworth, Jason C.; Dritz, Steven S.; Erceg, Jake A.; McKinney, L.; Smith, G. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2015)
A 3-wk study was conducted at a commercial feed mill in northwest Iowa to determine where the formation of fines occurs during pelleted feed manufacturing and if differences are present in nutrient composition between fines and pellets. During the study, 1,781pelleted feed samples were collected from 4 swine and 2 turkey diets. Samples were collected from 4 different locations throughout the mill to determine progression of fines formation during the manufacturing process. These locations included the pellet mill, pellet cooler, fat coater, and at load-out. Samples were taken on 7 to 10 different runs for each diet throughout the 3-wk period. Pellet durability index (PDI) and percentage fines were determined for all samples, and nutrient analysis was determined on a pooled sample from each run within diet. Nutrient analysis was determined via near-infrared spectroscopy (NIR) at the processing site and via wet chemistry at a commercial lab. Overall, PDI was different (P < 0.05) between locations in the mill. Pellet durability index increased from the pellet mill to the fat coater but then decreased between the fat coater and load-out. The largest increase in PDI was seen between the cooler and fat coater. Percentage fines decreased (P < 0.05) from the pellet mill to the cooler, but then increased as pellets went to the fat coater and then to load-out. The largest increase in fines was found between the cooler and fat coater and between the fat coater and loadout (5.6 and 6.5%). Dry matter and crude fiber were greater (P < 0.05) and fat tended to be greater (P < 0.08) in fines than in pellets as determined by NIR, whereas CP was significantly lower (P < 0.05) in the fines than in pellets. These differences were verified by wet chemistry results. Wet chemistry also found that fines tended to be higher (P < 0.05) in ADF, but fines were similar in Ca and P compared with pellets. In conclusion, fines increased as pellets were moved from the pellet mill to the load-out area. Pellet durability index improved from the pellet mill to the fat coater due to the removal of moisture in the pellet but then worsened at load-out, most likely due to the addition of fat, which may have started to soften the pellets. Both NIR and wet chemistry found that fines were higher in fiber and fat but lower in CP than pellets. These differences in nutrient content of the pellets compared with fines and the possibility of fines refusal at the feeder may lead to poorer pig performance. More research is needed to determine if fines formation can be reduced in the mill and if differences in nutrient composition of fines compared with pellets could lead to performance differences in pigs.
Swine Industry Day, 2014 is known as Swine Day, 2014
Keywords: Feed mill; Fines; Pelleting; Pellet durability index